STRUCTURAL-SEMANTIC FEATURES OF PHRASEOLOGICAL UNITS EXPRESSING INTELLECTUAL ABILITIES OF A HUMAN IN MODERN ENGLISH LANGUAGE (Web of Teachers: Inderscience Research, 2024)
The research studies the analysis of phraseological units with a component that reflects the intellectual abilities of a person. The main objective of the investigation is to study the structural and semantic features of phraseological units with a component that reflects the mental abilities of a person on the material of modern English.